PSYCHOLOGICAL CONTRACT FULFILLMENT, ORGANIZATIONAL IDENTIFICATION AND LECTURERS’ LOYALTY: A CONCEPTUAL MODEL FOR NIGERIAN UNIVERSITIES - Jakada, Muhammad Bello; Bambale, Abdu Ja’afaru; Ibrahim, Murtala Aminu; Liman, Amina (Kashere Journal of Management Sciences, 2024)
The purpose of this study is to propose a conceptual model that can help enhance lecturers’ loyalty in Nigerian Universities. After critically reviewing the extant literature, the study recognized the importance of psychological contract fulfilment (PCF) in enhancing employee loyalty (EL). Consequently, the study draws from social exchange theory (SET) and proposes a positive relationship between PCF and lecturers’ loyalty. However, prior studies argued that SET does not adequately explain employees’ responses to PCF. Therefore, the study supported SET with social identity theory (SIT) and proposes the mediating role of organizational identification (OI). The contribution of this study lies in supporting SET with SIT and suggests that employees' motivation to reciprocate PCF with positive attitudes and behaviour is transmitted by their identification with the organization. Furthermore, the study highlights to the policymakers the salience of PCF in overcoming the problem of lack of loyalty among lecturers.